Contemporary Miniatures : India & Pakistan - Steinrücke, Ranjana; The Fine Art Resource, Berlin (Berlin : The Fine Art Resource, 2003)
Sheikh, Gulam Mohammed ; Sheikh, Nilima ; Latif Qureshi, Nusra ; Abbas, Hamra ; Rathore, Talha ; Ahsan, Fasih ; Gera Baswani, Manisha ; Ray, Anandjit ; Butt, Ambreen
Biog., tent., coll., bibliog. [4 p.]
Published on the occasion of the exhibition "Contemporary Miniatures: India & Pakistan" at the The Fine Art Resource in Berlin, 10.04.2003 - 30.06.2003
boek